Brown dwarf census with the Dark Energy Survey year 3 data and thethin disc scale height of early L types - Carnero Rosell, Aurelio (2019)
In this paper we present a catalogue of 11 745 brown dwarfs with spectral types rangingfrom L0 to T9, photometrically classified using data from the Dark Energy Survey (DES)year 3 release matched to the Vista Hemisphere Survey (VHS) DR3 and Wide-field InfraredSurvey Explorer (WISE) data, covering≈2400 deg2up toiAB=22. The classification methodfollows the same phototype method previously applied to SDSS-UKIDSS-WISE data. Themost significant difference comes from the use of DES data instead of SDSS, which allowus to classify almost an order of magnitude more brown dwarfs than any previous search andreaching distances beyond 400 pc for the earliest types. Next, we also present and validate theGalmodBDsimulation, which produces brown dwarf number counts as a function of structuralparameters with realistic photometric properties of a given survey. We use this simulation toestimate the completeness and purity of our photometric LT catalogue down toiAB=22, aswell as to compare to the observed number of LT types. We put constraints on the thin disc scaleheight for the early L (L0–L3) population to be around 450 pc, in agreement with previousfindings. For completeness, we also publish in a separate table a catalogue of 20 863 M dwarfsthat passed our colour cut with spectral types greater than M6. Both the LT and the late Mcatalogues are found at DES release page https://des.ncsa.illinois.edu/releases/other/y3-mlt.